Methodological Status of Moral Psychology Scales in Iran: A Systematic Review - hamid Rafiei-honar; Hamidraza Hasanabadi (اخلاق وحیانی)
The purpose of the study was to investigate the conceptual and psychometric status of ethics scales in Iranian research from 1350 to 1399. The research method was a systematic review based on the COSMIN checklist in three indexes of validity, reliability, and responsiveness in the form of 9 parameters involving content validity, internal consistency, relative measures, measurement error, structural validity, hypotheses testing, cross-cultural validity, criterion validity, and responsiveness. Research data were identified in six steps and 92 scales were selected. Findings showed that of all scales (intra-person, 37 scales; inter-person, 26 scales; and socio-organizational, 29 scales) only the internal consistency parameter could be observed in more than 70% of cases, and the results were positive. After that, conceptualization, content validity, and hypothesis testing were considered in 50% of the scales, and the results were positive. Other parameters were not calculated in most reports, the information is not available, or their review is not relevant. In the present study, no "desirable" scale was identified that considered all the relevant parameters of COSMIN; only 5% of the scales are "acceptable", 40% are "in need of completion", 30% are "in need of re-examination", and 25% are "in need of detailed information". Therefore, if the percentage of scales that need to be completed is added to the acceptable scales, it can be claimed that 45% of Iranian ethics scales have the potential to be used; And the rest need to review or provide detailed information for evaluation and judgment.